Membangun Jiwa PEKA (Produktif, Edukatif, Kooperatif, Adaptif) melalui Program KKN di Rusun PIK Pulogadung - Amana Rohma; Nirmala; Mohammad Alwi; Ade Fajar; Dzakwan; Diana Fauziyah; Achmad Rizky Putra; Insan Kamil; Zahra Qotrun Nada; Fauzan Verdianto; Keissha Valda Tursida; Allifya Nurrizqiana; Muhamad Akbar Dimassyah (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Devotion to the community through a real work lecture (KKN) is one form of student contribution to overcoming the problems in the community. This study aims to examine the role of KKN in building sensitive souls (productive, educative, cooperative, adaptive) in Pik Pub Pub Rusun. The method used in this study is observation. KKN students participated in socialization activities, training of artwork, BTQ, healthy gymnastics, numerated literacy, seminars on early marriage and Islamic banking, futsal tournament, fun game (traditional game), Islamic competition (Azan, MHQ, Islamic puzzle, and coloring calligraphy), and badminton. The results showed that through KKN, KKN students can take advantage of the potential received during college by applying it in the community, so that it can ducto in and help resolve the problems that exist in the community, through students to get speech and participation from the very good community of programs implemented, and through KKN community can increase productive, educative, cooperative, and adaptive.